Pengaruh Variasi Sudut Input Sudu Mangkok Terhadap Kinerja Turbin Kinetik - Anam, Asroful; Soenoko, Rudy; Widhiyanuriyawan, Denny (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
The most of renewable energy in Indonesia is hydro which all potential is for about 75000- 76000 MW. But the use of that potential is 3,783 MW of large-scale and 220 MW of small-scale only. The use of small-scale hydro energy is river flows which has speed with ranges 0.01 - 2.8 m/s and used for a source of electrical energy by kinetic turbines. Kinetic turbine is one of water turbines but it uses speed of river flows for changing the water’s kinetic energy into mechanic one. The performances of the kinetic turbines depends on many factors and one of them is the using of blades on the runner. Turbine with a cup blade, river flows mashes the blade and changes momentum that can provide the runner rotating. On that process, there is energy change, here is kinetic energy of river flows into mechanical one and produces electricity energy by a generator. So the purpose of this study is to determine the effect of kinetic turbine performance with a cup blade input corner variations. The results of this study indicates that the kinetic turbine with a cup blade input corner 10 o is the highest or maximum performance than 15 o and 20 o , because the cup blade input corner 10 o has much mass flows mashing and striking the blade and the kinetic turbine with cup blade input corner 20 o is the minimum performance.Keywords: Kinetic turbine, Turbine performance, bowl blade, input corner.